2009
DOI: 10.1167/iovs.08-2793
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of a Tissue-Engineered Corneal Endothelium Reconstructed on a Devitalized Carrier in the Feline Model

Abstract: This study provides evidence for the short-term (7-day) anatomic and functional success of corneal transplantation with a tissue-engineered corneal endothelium reconstructed on a devitalized carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 52 publications
(53 reference statements)
0
33
0
1
Order By: Relevance
“…TE-HCE transplants were capable of recovering the corneal transparency of PCEP rabbits, maintaining the transparency of corneas for longer than previously reported (Aboalchamat et al, 1999;Ishino et al, 2004;Fu et al, 2006;Koizumi et al, 2008;Fan et al, 2009b;2010b;Proulx et al, 2009). The corneas of TE-HCE eyes became thinner and thinner with the time, while the corneas of PCEP and PKP eyes remained almost unchanged in thickness.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…TE-HCE transplants were capable of recovering the corneal transparency of PCEP rabbits, maintaining the transparency of corneas for longer than previously reported (Aboalchamat et al, 1999;Ishino et al, 2004;Fu et al, 2006;Koizumi et al, 2008;Fan et al, 2009b;2010b;Proulx et al, 2009). The corneas of TE-HCE eyes became thinner and thinner with the time, while the corneas of PCEP and PKP eyes remained almost unchanged in thickness.…”
Section: Discussionmentioning
confidence: 62%
“…Diverse types of cells and various scaffold carriers have been combined previously and a therapeutic efficiency of about one week of maintenance of corneal transparency has been attained in rabbit (Aboalchamat et al, 1999;Ishino et al, 2004;Koizumi et al, 2008;Fan et al, 2009b;Proulx et al, 2009). Unfortunately, all the previous trials fell well short of a clinical therapy for PCEP; the immortalized seed cells were either potentially tumorigenic or limited in number after primary culture or 4-5 rounds of subculture (Fan et al, 2007;2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-engineered feline corneal endothelium using cultured feline CECs seeded onto devitalized cadaver human stromal cornea achieved a cell density of 2272Ϯ344 cells/ mm 2 and expressed characteristic function-related markers such as Na ϩ K ϩ -ATPase and ZO-1 (105). A subsequent report showed functional success when the tissue-engineered feline corneal endothelium, reconstructed on a devitalized human stromal carrier, was transplanted into a feline model (104). Elsewhere, Honda et al (106), using cultured HCECs seeded onto fresh human corneal stromal discs, showed promising results when HCECs-populated stromal disc was transplanted into a rabbit model.…”
Section: Prospects For Corneal Endothelial Transplantation Using Cultmentioning
confidence: 97%
“…It is well established that HCECs retain their capacity to proliferate in vitro (30,64,97,104), and their growth dynamics are now better understood (29,42,76). Although primary HCECs cannot be propagated indefinitely, in the context of tissue-engineered corneal endothelial grafts, the use of nontransformed cells is advantageous over the use of transfected or immortalized HCEC-lines in the uncontrollable CEC growth observed (42).…”
Section: A Feasible Future For Tissue-engineered Corneal Endothelial mentioning
confidence: 99%
“…If positioning donor tissue in its anatomical position would not even be necessary, the concept of using a carrier to implant ex-vivo cultured endothelial cells into the recipient anterior chamber may become an ever more realistic approach [74][75][76][77][78].…”
Section: Future Perspectivesmentioning
confidence: 99%